Effect of virgin coconut oil as a natural additive on the quality of Murrah buffalo (Bubalus bubalis) liquid semen using tris-egg yolk extender - dian tria fatmila; A Trisna; K J Simanjuntak; W H Sutanto (Talenta Publisher, 2025)
Artificial insemination (AI) is an important technology in increasing the population and productivity of Murrah buffalo in Indonesia, however its success is also influenced by the quality of the semen during storage. The addition of virgin coconut oil (VCO) as a natural antioxidant in Tris-egg yolk extender has the potential to increase the stability of spermatozoa cells against oxidative stress. This study aims to evaluate the effect of VCO on the quality of Murrah buffalo liquid semen during 0, 24, and 48 hours storage at 3–5 °C. The study used a Completely Randomized Design (CRD) with five treatments (T0: control without VCO, T1: 8% VCO, T2: 10% VCO, T3: 12% VCO, and T4: 14% VCO) and four replicates. The results of the study showed that the addition of VCO at a dose of 8% (T1) had a positive effect on maintaining semen quality for up to 48 hours. The highest motility was recorded at T1 (57.00±1.54%) which was significantly different (P<0.05) with other treatments. T1 treatment (55.37±4.16) (P<0.05) significantly improved sperm viability at 24 to 48 hours. T2 (5.17±1.29) and T1 (4.80±0.71) treatments significantly improved sperm viability at 24 hours of storage, while T1 (6.24±0.88) was more effective in maintaining viability for up to 48 hours. Similarly, intact plasma membranes were maintained at T0 (41.75±0.68) and T1 (40.79±2.02) with significant differences (P<0.05) with other treatments at 48-hour storage. Overall, the addition of VCO in optimal concentrations was able to slow down the degradation of semen quality during storage in Murrah buffalo, demonstrating its potential as an effective and environmentally friendly natural additive antioxidant in sustainable Murrah buffalo liquid semen extender